2008
DOI: 10.2340/00015555-0354
|View full text |Cite
|
Sign up to set email alerts
|

Holmium Laser Treatment of Genital Warts: an Observational Study of 1500 Cases

Abstract: The treatment and relapse rate of genital warts are significant problems. The aim of this observational study was to assess the efficacy of holmium laser treatment of genital warts. A total of 1500 outpatients with genital human papillomavirus-induced lesions presenting from August 2002 to June 2005 were treated with holmium laser. The effects and side-effects of treatment were observed and analysed. Of this large cohort, lesions were excised at the first visit in 1488 cases. Twelve cases were treated a second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 9 publications
(4 reference statements)
1
14
0
Order By: Relevance
“…Holmium laser treatment is one of the effective methods for the treatment of genital warts . The treatment of giant genital warts usually requires 3 to 4 weeks of recovery time after holmium laser treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Holmium laser treatment is one of the effective methods for the treatment of genital warts . The treatment of giant genital warts usually requires 3 to 4 weeks of recovery time after holmium laser treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed recurrence rates of 3%-77%, 20%-79%, 8%-35% and 23%-70% when lesion treatment had done with holmium laser, cryotherapy, conventional surgery and podophyllin respectively. 7,11,16,20 The results of this study showed treatment with holmium laser is correlated with highest clearance rate (92.2%) and lowest recurrence rate (14.3%) than other applied treatments. In conclusion, holmium laser is safe, and more effective, than other methods in management of genital warts.…”
Section: Discussionmentioning
confidence: 57%
“…Mechanism of this advanced technology is photothermal destruction, that makes it possible to remove even the largest warts. 11 However, there are few studies about the use of holmium laser in the treatment of genital warts. This retrospective study compared the success rate of holmium laser with other genital wart treatments.…”
Section: Introductionmentioning
confidence: 99%
“…This laser has been used for treatment of genital warts in our clinic for 6 years, with a satisfactory curative effect, especially in the treatment of giant genital warts. 11 In conclusion, PG in laser-treated PWSs is a rare condition. Although there are several reports of adverse effects and complications of 595-nm PDL treatment, PG has not been documented as a side effect or complication.…”
Section: Discussionmentioning
confidence: 89%